The Role of Internal Motivation in Mediating The Influence of Competency and Training on Employee Productivity - Dewi, Puspa; Apriansyah, Roky; Ningsih, Fitria (ADPEBI International Journal of Business and Social Science, 2024)
This research aims to test hypotheses and analyze the role of internal motivation in mediating the influence of competency and training on employee productivity at PT. Mukti Lestari Desa Harapan Jaya Kabupaten Indragiri Hilir. Desain/Metodologi/Pendekatan – The population used in this study were all employees of PT Mukti Lestari Harapan Jaya Village, Indragiri Hilir Regency. The sampling method used is the census method or saturated sample, the sample in this study was 45 people. The variables used in compiling statements include variables about competence, training, internal motivation and productivity with a Likert scale of 1-5. productivity with a Likert scale of 1-5. Findings– In this research it is known that 1) competency has an effect on productivity, 2) training has an effect on productivity, 3) Competency has an indirect effect on employee productivity with internal motivation as a mediating variable, 4) Training has an indirect effect on employee productivity with internal motivation as a mediating variable.. Research limitations– Limitations in this research are: this research only uses competency, training, internal motivation and productivity variables, so for further research it is hoped that there will be additional variables such as work environment, organizational commitment, working hours and others. Originality/value– This research uses internal motivation as a mediating variable and employee productivity as the dependent variable so this research is different from previous research.